2001
DOI: 10.1080/09553000010024687
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic radiosensitization: mode of action and clinical relevance

Abstract: Since recent phase III clinical trials have shown significant benefit of adding hyperthermia to radiotherapy regimens for a number of malignancies, it will become more important again to determine the molecular effects underlying this success. Such information could eventually also improve treatment quality in terms of patient selection, improved sequencing of the heat and radiation treatments, the number of heat treatments, and multimodality treatments (i.e. thermochemoradiotherapy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
155
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(161 citation statements)
references
References 84 publications
4
155
1
1
Order By: Relevance
“…In addition to complementary biologic effects with radiation and chemotherapy, mechanisms for direct effect include protein denaturization including inhibition of sub-lethal and potentially lethal damage repair through inactivation of DNA repair pathways leading to mitotic catastrophe, induction of senescence, apoptosis, and necrosis. (21)(22)(23)(24)(25)(26)(27)(28) Research has revealed that protein denaturization is a key biologic effect of hyperthermia at modest temperature elevations. (29) The activation energeries for protein denaturization and heat induced cell death were noted to be within the same range.…”
Section: Mechanism Of Cell Death With Hyperthermiamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to complementary biologic effects with radiation and chemotherapy, mechanisms for direct effect include protein denaturization including inhibition of sub-lethal and potentially lethal damage repair through inactivation of DNA repair pathways leading to mitotic catastrophe, induction of senescence, apoptosis, and necrosis. (21)(22)(23)(24)(25)(26)(27)(28) Research has revealed that protein denaturization is a key biologic effect of hyperthermia at modest temperature elevations. (29) The activation energeries for protein denaturization and heat induced cell death were noted to be within the same range.…”
Section: Mechanism Of Cell Death With Hyperthermiamentioning
confidence: 99%
“…Specifically, heat induces changes in DNA repair foci such as the MRN complex which includes MRE11, rad 50, and nbs1, key proteins involved in double strand break repair, the nucleolus and on the complexes that anchor DNA to the nuclear matrix thus contributing to radiosensitization. (33)(34) Chromosomal aberrations may also occur due to heat sensitivity of the centriole. (35) Failure of DNA replication in S-Phase of the cell cycle results in mitotic catastrophe.…”
Section: Mechanism Of Cell Death With Hyperthermiamentioning
confidence: 99%
“…Agents inhibiting DNA repair processes potentiate the cytotoxicity of DSBs in cancer therapy (3). Elevated temperature is one such agent that, via unclear mechanisms, interferes with multiple pathways of DNA repair (4)(5)(6) and is clinically applied (7).…”
mentioning
confidence: 99%
“…It also has the ability to kill cells under conditions of hypoxia and low pH, which in turn are reasons for developing resistance to radiation and chemotherapy (Kampinga 2001). Hyperthermic temperatures of 43 °C have been shown to have more than an additive or synergistic cytotoxic effect when employed with several anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of optimal timing of hyperthermia and other therapies, Overgaard et al showed that application of hyperthermia at 42-43 °C three to four hours after radiation was optimal for radiosensitization of cells (Overgaard 1982). Radiosensitization and chemosensitization to DNA-intercalating agents such as DOX both result in cytotoxic effects by preventing DNA damage repair mechanisms (Kampinga 2001;Blasiak, Widera et al 2003). Therefore, the optimal timing between chemotherapy and hyperthermia can be expected to be similar to the timing between radiotherapy and hyperthermia.…”
Section: Introductionmentioning
confidence: 99%